Managed C++ and .NET Development - Fraser, Stephen R.G. (Apress, 2012)
This book is about writing .NET applications. It's designed to start you with a clean slate, wiping away any need for developing COM, DCOM, COM+, or ActiveX components. Instead, it shows you how to code in the world of .NET, free of all that unneeded baggage.